Dietary supplementation of β-1, 3-glucan improves the intestinal health of white shrimp (Litopenaeus vannamei) by modulating intestinal microbiota and inhibiting inflammatory response - Shen, Kaikai; Bao, Lixin; Liu, Muxin; Lei, Wen; Zhou, Qin; Ding, Jiali; Fang, Peng; Hu, Baoqing; Wen, Chungen; Kumar, Vikas; Peng, Mo; Yang, Gang (Frontiers in Immunology, 2023)
The phenomenon of intestinal dysfunction is widely observed in white shrimp (Litopenaeus vannamei) culture, and β-1,3-glucan has been confirmed to be beneficial in intestinal health with a lack understanding of its underlying mechanism. Proteobacteria, Firmicutes, and Actinobacteria served as the predominant phyla inhabiting the intestine of white shrimp, whilst a significant variation in their proportion was recorded in shrimp fed with basal and β-1,3-glucan supplementation diets in this study. Dietary supplementation of β-1,3-glucan could dramatically increase the microbial diversity and affect microbial composition, concurrent with a notable reduction in the ratio of opportunistic pathogen Aeromonas, gram-negative microbes, from Gammaproteobacteria compared to the basal diet group. The benefits for microbial diversity and composition by β-1,3-glucan improved the homeostasis of intestinal microbiota through the increase of specialists’ number and inhibition of microbial competition caused by Aeromonas in ecological networks; afterward, the inhibition of Aeromonas by β-1,3-glucan diet dramatically suppressed microbial metabolism related to lipopolysaccharide biosynthesis, followed by a conspicuous decrease in the intestinal inflammatory response. The improvement of intestinal health referred to the elevation in intestinal immune and antioxidant capacity, ultimately contributing to the growth of shrimp fed β-1,3-glucan. These results suggested that β-1,3-glucan supplementation improved the intestinal health of white shrimp through the modulation of intestinal microbiota homeostasis, the suppression of intestinal inflammatory response, and the elevation of immune and antioxidant capacity, and subsequently promoted the growth of white shrimp.